PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM LITERASI KEUANGAN EDUKASI INVESTASI SYARIAH BERSAMA PEGADAIAN SYARIAH DI PEKANBARU - Teuku Reza Kurniawan; Yulia Harwina; Diana Sri Dewi; Nova Syafrina; Eka Putra; Siti Rofidah; Abdul Aziz; Jenita Jenita (Jurnal Pengabdian Kompetitif, 2026)
This Community Service Program (CSP) aims to enhance Islamic financial literacy and investment competencies through an experiential learning approach. The program was implemented through a collaborative partnership between STIE Riau and Pegadaian Syariah involving participants from the community and academic environment. The implementation methods included educational sessions, product socialization, hands-on practice using the Pegadaian Syariah digital application, and interactive discussions on Islamic investment products, particularly Gold Savings and Sharia Rahn contracts. Program evaluation was conducted through participatory observation, assessment of conceptual understanding, and measurement of participants’ practical skills. The results indicate a high level of participant engagement, a significant improvement in digital application usage competence, and a strong understanding of Sharia-compliant investment mechanisms. In addition, participants demonstrated high interest and enthusiasm toward the learning materials delivered. These findings suggest that the experiential learning-based approach and campus–industry collaboration are effective in strengthening Islamic financial literacy and reshaping public perceptions of Pegadaian Syariah as an inclusive and modern Islamic investment platform. This program can serve as a replicable model for community-based Islamic financial education initiatives.